Innovative nanostructured lipid carrier gel for enhanced topical delivery of roflumilast in psoriasis management - Abhishek Singh; Anurag Verma; Prashant Kumar (Journal of Applied Pharmaceutical Research, 2025)
Background: Psoriasis is a chronic immune-mediated skin disorder marked by keratinocyte hyperproliferation, inflammation, and oxidative stress, causing erythematous, scaly plaques that impair quality of life. Current therapies have side effects and poor solubility, highlighting the need for improved topical delivery systems. Methodology: An NLC-based gel encapsulating the PDE4 inhibitor roflumilast was developed for enhanced topical delivery. NLCs were prepared by high-pressure homogenization with oleic acid, glycerol monostearate, and Tween 80, and incorporated into a Carbopol 934 gel. The physicochemical properties, encapsulation efficiency, in vitro release, and in vivo efficacy of imiquimod in imiquimod-induced psoriatic rats were evaluated. Results: The developed gel was homogeneous, white, and transparent, with a dermally compatible pH (5.36-5.85), optimal viscosity (3.5-14.5 Pa·s), and good spreadability (4.3-7.2 g/cm/s). Formulation F3 showed high encapsulation efficiency (90.38 ± 2.91%) and sustained drug release (~90% over 24 hours). Drug content ranged from 72% to 95%. Ex vivo skin permeation studies demonstrated enhanced roflumilast penetration. In vivo application led to a significant reduction in psoriasis area and severity index (PASI) scores from 6.5 on Day 1 to 1.6 on Day 9. No signs of erythema, edema, or rashes were observed during the 72-hour skin irritation study, confirming excellent dermal compatibility. Histopathology confirmed decreased inflammation, reduced hyperkeratosis, and restored epidermal architecture.  Discussion: The NLC-based roflumilast gel showed favorable physicochemical and biopharmaceutical properties, offering improved delivery and sustained release over conventional psoriasis therapies. Conclusion:  Roflumilast-NLC gel is a promising topical therapy for psoriasis with controlled release and enhanced skin retention.